2021
DOI: 10.3390/met11101574
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal Scheme Effect on the Biomechanical Response of Full-Arch Dental Prosthesis Supported by Titanium Implants: A Systematic Review

Abstract: Dental implant-supported prosthesis are widely used in oral reconstruction of totally edentulous patients. Nonetheless, one of the most common failures in these cases is caused by overloading from improper occlusion. The aim of this work was to determine if the occlusal scheme influences the biomechanical response in implant-supported dental prostheses. Searches were conduct is several databases (PubMed/MEDLINE, The Cochrane Library, Web of Science, Scopus, LILACS, and Opengrey). We found 632 publications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Implant prostheses rehabilitation has proven efficacy in the treatment of fully edentulous patients in long-term studies [ 1 , 2 ]. However, the process of bone resorption due to physiological and pathological factors [ 3 ] complicates planning for the installation of posterior implants as a prosthetic support [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Implant prostheses rehabilitation has proven efficacy in the treatment of fully edentulous patients in long-term studies [ 1 , 2 ]. However, the process of bone resorption due to physiological and pathological factors [ 3 ] complicates planning for the installation of posterior implants as a prosthetic support [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the titanium is the most used material due to its mechanical characteristics as strength and resistance to distortion. Systematic reviews have shown excellent results promoting titanium abutments as highly reliable [4][5][6]; however, sometimes it is necessary to replace it by other materials. The usage of titanium as substrate can generate a gray zone effect on the peri-implant marginal mucosa, dampening the treatment aesthetics and the patient satisfaction [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of data evaluating the influence of metallic link height on the mechanical behavior of these restorative systems before and after the fatigue cyclic [17]. It is also noteworthy that restorative materials fail under fatigue, especially with lower intensity loads applied for a long period [18][19][20]. In addition, the abutment design may influence the marginal bone loss; however, it is still unclear how this parameter affects the stresses in the peri-implant tissues [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is important for clinicians to identify how occlusal force (normal or excessive) may impact implant success rates. Therefore, for a stable dental treatment, it is important to avoid overloading the dental implants and the bone, which can lead to biological and mechanical problems [20]. In summary, dental implants are exposed to inconstant loading during their life span due to chewing, which may lead to mechanical failure under fatigue [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation